Development of a UHPLC–MS/MS (SRM) method for the quantitation of endogenous glucagon and dosed GLP-1 from human plasma. (May 2017) - Howard, James W; Kay, Richard G; Jones, Ben; Cegla, Jaimini; Tan, Tricia; Bloom, Steve; Creaser, Colin S
Aim: The performance of glucagon and GLP-1 immunoassays is often poor, but few sensitive LC–MS/MS methods exist as alternatives.Experimental : A multiplexed LC–MS/MS method using a 2D extraction technique was developed.Results: The method was established for the quantitation of endogenous glucagon (LLOQ: 15 pg/ml) and dosed GLP-1 (LLOQ: 25 pg/ml) in human plasma, and is the first such method avoiding immunoenrichment. Specificity of endogenous glucagon quantitation was assured using a novel approach with a supercharging mobile phase additive to access a sensitive qualifier SRM. Endogenous glucagon concentrations were within the expected range, and showed good reproducibility after extended sample storage. A cross-validation against established immunoassays using physiological study samples demonstrated some similarities between methods.Conclusion: The LC–MS/MS method offers a viable alternative to immunoassays for quantitation of endogenous glucagon, dosed glucagon and/or dosed GLP-1.